Relationship between leaf life-span and photosynthetic activity of Quercus ilex in polluted urban areas (Rome). (Environmental pollution (Barking, Essex : 1987), 2000)
Anatomical, morphological and physiological leaf traits of Quercus ilex in response to different traffic levels (high traffic level, type A sites; average traffic level, type B sites; control sites, type C sites) were analysed in Rome. Superficial leaf deposits were analysed comparing unwashed and washed leaf samples. Washing lowered Pb 61% in A, 54% in B and 27% in C. Sr, Fe, Cu, Zn and Al showed the same trend as Pb. The higher photosynthetic activity of 1-year-old leaves (Pn=7.0+/-2.9 micromol m(-2 )s(-1), average value) in A sites with respect to B sites (6.7+/-2.4 micromol m(-2 )s(-1)) and C sites (6.7+/-1.8 micromol m(-2 )s(-1)) seems to be related to higher stomatal conductance (g(s)=0.13+/-0.06 mol m(-2 )s(-1)), higher total chlorophyll content (Chl=1.57 mg g(-1)) and higher leaf thickness (L(T)=218.9 microm), particularly palisade parenchyma thickness (109.4 microm). Q. ilex showed, on average, 95% of 1-year-old leaves and rarely 2-year-old leaves in A and B sites; 77% 1-year leaves, 20% previous-year leaves and sporadic 3-year leaves in C sites. The enhanced leaf senescence in A sites is compensated by a stimulated shoot production (18% higher with respect to C sites); 25% increased specific leaf area seems to be compensatory growth occurring in order to increase the size of the assimilatory area. The inverse trend of leaf life-span and Pn seems to be Q. ilex' adaptive strategy in polluted areas.